Thailand's 'English fever', migrant teachers and cosmopolitan aspirations in an interconnected Asia. Issue 5 (3rd September 2018) - Hickey, Maureen
ABSTRACT: Over the past decade, growing numbers of foreign-born English speakers from the Global South have begun migrating to Thailand to seek work as teachers in the region's booming Teaching English as a Foreign Language industry. As citizens of so-called outer circle English-speaking countries (former British and American colonies in Asia and Africa), these migrants enter the highly competitive and racially stratified Asian Teaching English to Speakers of Other Languages labor market at a significant disadvantage. In this paper I examine the growing demand for English education in Thailand and argue that it is best understood through an analysis of regional competition in a globally ascendant 'Asia'. Government responses have been marked by shifting and contradictory entry and employment requirements, resulting in uncertainty for foreigners seeking work as teachers in Thailand. However, this same uncertainty enables non-Western teachers to utilize Thailand as a site for migration and employment in ways not possible in other parts of the region.